Efektifitas Ekstrak Daun Rhizophora Mucronata Dalam Menghambat Pertumbuhan Aeromonas Salmonicida Dan Vibrio harveyi - Anisa Suciati; Wardiyanto -; Sumino - (University of Lampung, 2012)
Infectious diseases lead to reducing aquaculture productivity. The using of chemical antibiotic was avoided since their negative effect was known, i.e. created resistant bacteria, contaminating environment and fish meat. The purpose of the research is to find the active compound from Rhizophora mucronata leaf and their activity to inhibit pathogenic bacteria Aeromonas salmonicida and Vibrio harveyi. Extraction procedure conducted by using maceration technique to extract type of mangrove leaf (tip, main leaf, dried leaf), and organic solvent (hexan, ethylacetate, methanol). The result of this research showed that active compound from Rhizopra mucronata give negative response inhibiting Aeromonas salmonicida while postif to Vibrio harveyi . The tip of Rhizophora muncronata leaf is more effective to inhibit pathogenic bacteria, and ethylacetate is the best solvent to extract Rhizophora muncronata leaf. Lethal concentration (LC-50) from Rhizopra macronata is 200 ppm.